Differences of Legal Regulatiom in Financial Accounting and Corporate Income Tax - Endrijaitis, Martynas (Teisė, 2022)
This paper discloses cases in which permanent differences between the legal regulation of financial accounting and corporate income tax arise, while revealing the significance of these differences in the fulfillment of a tax liability (corporate income tax)